El enigma de la leontina: Flora Díaz Parrado - Boudet, Rosa Ileana (Latin American Theatre Review, 2005)
Irony, black humor, the cruel grimace --the theatre of Flora Díaz Parrado anticipates themes and theatrical forms of the vanguard, and it shares certain points and mysteries with the theatre of Carlos Felipe. With El velorio de Pura (1941) she cultivated a theatre of the body, of gestures, and not just the spoken word, while with Juana Revolico (1944) she added a broader concept of ritual. Beyond the realm of the literary world, she imagined magic, stage machinery and a range of oneiric, grotesque and fantastic elements incorporating traditional pop culture. Her works, scarcely studied or staged, demand another look within the context of Cuban playwriting. (RIB)